Body Mass Index, Waist Circumference, and Cognitive Decline Among Chinese Older Adults: A Nationwide Retrospective Cohort Study - Liang, Fang; Fu, Jialin; Moore, Justin B.; Zhang, Xinge; Xu, Yijia; Qiu, Nan; Wang, Yechuang; Li, Rui (Frontiers in Aging Neuroscience, 2022)
Background: The reported associations between BMI (body mass index), WC (waist circumference) and cognitive decline are not consistent, especially in older adults. Objective: To investigate the longitudinal associations of BMI, WC and their change values with cognitive decline among Chinese adults sixty and older and examine the potential moderating effect of sex on these relationships. Methods: This study participants were from the waves one to four (2011-2018) of the China Health and Retirement Longitudinal Study (CHARLS). Cognition function, BMI, and WC were measured at four examinations over seven years. Interview-based cognitive assessments of memory, orientation and attention, and visuospatial ability were recorded. Standardized global cognitive scores were generated. BMI and WC were objectively measured. Mixed-effects models were performed to evaluate the associations. Results: A final sample of 3035 Chinese older adults [mean (SD) age, 66.94 (5.43) years; 40.16% (n = 1219) women] were included. Higher BMI (estimate = 0.0107; SE = 0.0024; p < 0.0001) and WC (estimate = 0.0019; SE = 0.0006; p = 0.0037) were associated with slower cognition score decline over the seven-year follow-up, while greater BMI variability (estimate = -0.0365; SE = 0.0116; p = 0.0017) was related to faster cognition score decline. The results were not modified by sex. BMI-defined overweight (estimate = 0.0094; SE = 0.0043; p = 0.0298) was associated with a slower cognition score decline, and large weight gain (estimate = -0.0266; SE = 0.0074; p = 0.0003) and large WC loss (estimate = -0.0668; SE = 0.0329; p = 0.0426) both were associated with faster cognition score decline. Conclusions: Among Chinese older adults, higher BMI, higher WC, and overweight are related to slower cognitive decline, while greater BMI variability, large weight gain, large WC loss are associated with faster cognitive decline.